1999
DOI: 10.1111/j.1528-1157.1999.tb00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitive and Nonphotosensitive Electronic Screen Game‐Induced Seizures

Abstract: Summary:Purpose: To disclose possible epileptologic differences between photosensitive and nonphotosensitive patients with seizures induced by electronic screen games (ESGs).Methods: In patients with ESG-induced seizures who showed photo-and pattern sensitivity, magnetoencephalography (MEG) and EEG were performed simultaneously during ESG play, and equivalent current dipoles (ECDs) of the MEG spikes were estimated. In patients without ESG-induced seizures, who were surgical candidates, the intracranial EEG was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Neurophysiologic evaluations such as transcranial magnetic stimulation (TMS) (Siniatchkin et al., 2007; Shepherd & Siniatchkin, 2009), evoked potentials (Guerrini et al., 1998; Porciatti et al., 2000), or fMRI (Chiappa et al., 1999; Moeller et al., 2009a,b) have indicated the increased involvement of the primary recipient occipital cortices of light stimuli in PS patients. However, most of these works (and other hemodynamic and neurophysiologic studies) found that extraoccipital cortices and subcortical structures are also involved in the hyperexcitability mechanism (Kapucu et al., 1996; Chiappa et al., 1999; Inoue et al., 1999; Holmes et al., 2010). Frontal or premotor cortices are certainly involved in the direct generation of spike and wave discharges, including those evoked by PS in patients with generalized epilepsies, as has been directly demonstrated by inspectional EEG analyses (Niedermeyer, 1996; Kasteleijn‐NolstTrenité, 1998) or quantitative methods (Gotman, 1981; Takasaka et al., 1989; Visani et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Neurophysiologic evaluations such as transcranial magnetic stimulation (TMS) (Siniatchkin et al., 2007; Shepherd & Siniatchkin, 2009), evoked potentials (Guerrini et al., 1998; Porciatti et al., 2000), or fMRI (Chiappa et al., 1999; Moeller et al., 2009a,b) have indicated the increased involvement of the primary recipient occipital cortices of light stimuli in PS patients. However, most of these works (and other hemodynamic and neurophysiologic studies) found that extraoccipital cortices and subcortical structures are also involved in the hyperexcitability mechanism (Kapucu et al., 1996; Chiappa et al., 1999; Inoue et al., 1999; Holmes et al., 2010). Frontal or premotor cortices are certainly involved in the direct generation of spike and wave discharges, including those evoked by PS in patients with generalized epilepsies, as has been directly demonstrated by inspectional EEG analyses (Niedermeyer, 1996; Kasteleijn‐NolstTrenité, 1998) or quantitative methods (Gotman, 1981; Takasaka et al., 1989; Visani et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We used the lamp with circular reflector that delivers flashes with an intensity of 0.70 Joule which at 30 cm from the nasion of the patient. IPS was performed with frequencies of 1,2,4,8,10,12,15,18,20,25,40,50, and 60 flashes/ s, and 0.5 and 70 Hz filters were used. Each frequency was performed with an interval of at least 7 s between each frequency, and each application was continued for 10 s, during which the eye was kept open in the first five seconds and closed in the last five seconds.…”
Section: Methodsmentioning
confidence: 99%
“…There are numerous studies suggesting that PPR is related with extreme excitability and reactivity in the visual cortex [12,13]. Moreover, it has been revealed in several studies that during the PPR, functional changes and changes in the blood stream occur in the supplementary motor area (SMA), the perisylvian area and medial temporal areas, besides the occipital cortex [14][15][16]. Strigaro et al documented a defective inhibition in the visual system of photosensitive patients with IGE, using a new VEP technique (Faired pulse flash -VEP) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Their findings were consistent with the idea that normal synchronized activity of large numbers of cells brought about by repetitive visual stimulation (evidenced by the harmonic gamma activity) results in a failure of inhibitory processes and culminates in the pathologic synchronization of the epileptic discharge. MEG was used by Inoue and associates (89) to investigate localization of electronic screen game-induced spikes. Patients who were photosensitive had MEG-documented posterior predominance of source dipoles in patients who had spikes during electronic screen games (89), but additional dipoles were localized to the supplementary motor area, perisylvian region, and medial temporal lobe.…”
Section: Mechanisms Of Photosensitivitymentioning
confidence: 99%
“…MEG was used by Inoue and associates (89) to investigate localization of electronic screen game-induced spikes. Patients who were photosensitive had MEG-documented posterior predominance of source dipoles in patients who had spikes during electronic screen games (89), but additional dipoles were localized to the supplementary motor area, perisylvian region, and medial temporal lobe.…”
Section: Mechanisms Of Photosensitivitymentioning
confidence: 99%